Anticoagulant Efficacy and Immunogenicity of the Selective Factor Xa Inhibitor Antistasin Following Subcutaneous Administration in the Rhesus Monkey - Dunwiddie, Christopher T; Nutt, Elka M; Vlasuk, George P; Siegl, Peter K S; Schaffer, Linda W (Thrombosis and Haemostasis, 1992)
The antithrombotic efficacy and duration of action of a single subcutaneous administration of the selective factor Xa inhibitor recombinant antistasin (rATS) was evaluated in a rhesus monkey model of mild disseminated intravascular coagulation. rATS (1 mg/kg) was shown to be fully effective and comparable to standard heparin (1,000 U/kg) in the suppression of thromboplastin-induced fibrinopeptide A generation for at least 5 h following a single subcutaneous administration. The absorption rate of rATS, as measured by ex vivo activated partial thromboplastin times (aPTT), mirrored that of standard heparin exhibiting peak anticoagulant activity between 1 and 2 h post administration. The anticoagulant effects of a single rATS dose lasted for longer than 30 h maintaining an aPTT value at least 2-fold higher than baseline. Repeated subcutaneous administrations of rATS resulted in the generation of fully neutralizing antibodies. These results suggest that specific factor Xa inhibition may be as effective as standard heparin in the treatment of venous thrombosis. Due to its antigenicity however, rATS is probably not suitable for chronic subcutaneous anticoagulant therapy.